Beta-lactam susceptibility of Neisseria gonorrhoeae isolates from pelvic inflammatory disease. - Pinon, G (1981)
Gonococci isolated in France from urethral and endocervical cultures in 12 women with pelvic inflammatory disease were similar, in their susceptibility to six beta-lactam antibiotics as determined by an agar dilution procedure, to isolates from patients with uncomplicated anogenital infections (83 patients). These data contrast with earlier study done in the United States.